An assessment of the Determinants of Inflation in Nepal: A study between 1974/75 and 2021/22 - Chhetri, Hom Bahadur (Kalika Journal of Multidisciplinary Studies, 2023)
Inflation is one of the important and interestingly touchy macroeconomic variables that influences other macroeconomic variables such as investment, consumption, saving and others. Therefore, it has become renewed interest in recent years mainly for both developed and developing countries. This paper examined the short-run and long-run relationship between inflation and its determinants in Nepal using time series data over the period of 1974/75-2021/22. The ARDL bound test approach to co-integration and error correction model have been used to examine the long-run and short-run relationship between variables. The results from ARDL bound test approach to co-integration show that broad money supply, Indian inflation and budget deficit have a significant positive effect on inflation while exchange rate negatively affect it in the long-run. The result from error correction model also found that Nepalese inflation and Indian inflation are significantly and positively related even in the short-run. However, real GDP affects inflation negatively as expected but it is statistically insignificant. A corollary of the results is that broad money supply, budget deficit, Indian inflation and exchange rate are the main drivers of inflation in Nepal.